Is sports sponsorship effective? Effects on brand equity and engagement on Twitter - Vega Nuñez, Francisco; Andreu Simó, Luisa; Currás Pérez, Rafael (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
The purpose of this study was to analyze the impact of sports sponsorship in social networks on brand equity and engagement on Twitter. Specifically, it focuses on the effectiveness of Ecuadorian soccer sponsorship brands on the four dimensions of brand equity (awareness, loyalty, perceived quality and brand association) and consumer engagement. This empirical study was conducted through two online surveys of soccer fans, with two different stimuli: sponsoring brand (n=224) versus non-sponsoring brand (n=260). The findings indicated that the sponsoring brand presents a positive and significant impact on its brand equity and engagement on Twitter compared to the non-sponsoring brand. The study affirms that brand equity and consumer engagement can offer academics and industry practitioners a viable method for evaluating the effectiveness of sports sponsorship on social media.